As contribuições do PIBID de pedagogia da UFPA para inclusão de alunos no ensino regular e na formação de professores - SANTOS, Sulyane Palmeira dos (2020)
This article aims to reflect on the contributions of the Institutional Program of Initiation to Teaching Grant (PIBID) for the training of teachers in the Pedagogy course of the Federal University of Pará (UFPA) with a view to include students targeted public education Special. This experience occurred in a public school of basic education in the municipality of BelémPa, from 2016 to 2017, experienced as a scholarship holder of the Study and Research Group on Curriculum and Teacher Training in the Perspective of Inclusion (INCLUDERE), linked to the project "Teacher training for an inclusive school: collaborative actions between higher education and basic education in municipalities in Pará. The methodology persists in the report of the activities developed and bibliographical revision of the themes pertinent to the studies on special education and the formation of teachers. The PIBID provided exceptional and therefore productive experiences during the training process, giving fellows opportunities for insight, practice and reflection on the importance and necessity of training for the inclusion of students with special educational needs.